On The Relationship between Multiple Intelligences and Their Performance on Vocabulary Tests among Iranian EFL Learners (Global Journal of Human-Social Science, 2012)
MI theory refers to a learner-based philosophy that characterizes human intelligence as having multiple dimensions that must be acknowledged and developed in education. It developed in mid 1983s by Gardner. MI theory includes the concepts that intelligence is pluralistic, encompassing at least eight intelligences. One of the greatest applications of the theory of MI is in education in that it identifies the differences among people regarding their intelligence preferences and the role it might play in learning environment. Not many studies have concerned the role of MI in language learning. The present study investigated the relationship between participants’ MI and their performance on vocabulary tests. The participants were 100 junior students at KhoramabadAzad University majoring in English Language Teaching. They wereasked to answer the MIDAS developed by Shearer (1996). Then, they answered four different formats of vocabulary tests, namely, antonym, gap filling at sentence level, gap filling at context level, and matching formats.
Keywords: Intelligence; Multiple intelligences; Vocabulary test format